Giant g‐factor in Self‐Intercalated 2D TaS2. Issue 38 (21st August 2022) - Wang, Ziying; Wang, Zishen; Zhou, Xin; Fu, Wei; Li, Haohan; Liu, Chaofei; Qiao, Jingsi; Quek, Su Ying; Su, Chenliang; Feng, Yuanping; Loh, Kian Ping
Abstract: Central to the application of spintronic devices is the ability to manipulate spins by electric and magnetic fields, which relies on a large Landé g ‐factor. The self‐intercalation of layered transitional metal dichalcogenides with native metal atoms can serve as a new strategy to enhance the g ‐factor by inducing ferromagnetic instability in the system via interlayer charge transfer. Here, scanning tunneling microscopy (STM) and scanning tunneling spectroscopy (STS) are performed to extract the g ‐factor and characterize the electronic structure of the self‐intercalated phase of 2H‐TaS2 . In Ta7 S12, a sharp density of states (DOS) peak due to the Ta intercalant appears at the Fermi level, which satisfies the Stoner criteria for spontaneous ferromagnetism, leading to spin split states. The DOS peak shows sensitivity to magnetic field up to 1.85 mV T −1, equivalent to an effective g‐ factor of ≈77. This work establishes self‐intercalation as an approach for tuning the g‐ factor. Abstract : Central to the application of spintronics is the ability to manipulate spins by electric and magnetic fields, which relies on a large Landé g ‐factor. Through scanning tunneling microscopy studies, the self‐intercalated phase of 2H‐TaS2 shows sensitivity to magnetic field up to 1.85 mV T −1, equivalent to an effective g‐ factor of ≈77, which is 20‐folds larger than that of pristine 2H‐TaS2 .